Promoting The Students Speaking Skill By Implementing Collaborative Learning Method In Teaching Speaking Skill - Ayyub B; Erwin Akib; Bahrun Amin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research was aimed at knowing the implementation of Collaborative Learning promotes students’ speaking skill at the second semester English Education Department Muhammadiyah University of Makassar. This research applied a quasi-experimental design; the non-equivalent control group design. The sample was taken by using purposive random sampling technique. The total number of samples was 38 students of two classes consisting of class II G was experimental class and II C was the control class. There was speaking test as the instrument. The statistical result analysis of SPSS 25 showed that in accuracy sig 2-tailed = 0.000 is less than 0.05 and in fluency sig 2-tailed = 0.000 is less than 0.05. This result rejects the first null hypothesis which states that there is no significant difference between the mean score of pretests and posttest of the students’ speaking skills. This research concluded that the use of Collaborative Learning in teaching speaking promote the students’ speaking skills in terms of accuracy and fluency.